Motivations, expectations, and experiences of labiaplasty: A qualitative study - Sharp, Gemma; Mattiske, J.; Vale, K. (Oxford University Press, 2016)
Background: The demand for labiaplasty has increased rapidly over recent years; however, very little is known about the experiences women have undergoing this surgery or the subsequent effects it has on their well-being. Objectives: To explore women's reasons for undergoing labiaplasty, their expectations, and preoperative and postoperative experiences. Methods: One-on-one semi-structured interviews were conducted with 14 adult women who had undergone a labiaplasty procedure. The women were asked about their reasons for having labiaplasty, the processes of accessing and undergoing surgery, and how various aspects of their lives were influenced after having surgery. The interviews were audio recorded then transcribed verbatim. The interview transcripts were analyzed using thematic analysis owing to the exploratory nature of the study. Results: Themes reflecting “media influence,” “negative commentary,” “physical vs appearance reasons,” “satisfaction with surgery,” and “sexual well-being” emerged from the analyses. Online media representations of labial appearance, and negative past experiences, primarily sexual in nature, contributed to women's concerns about their labial appearance. Issues of physical discomfort were also common and were sometimes emphasized to potentially legitimize women's requests for surgery. Most women were generally very satisfied with their surgical results, although some noted that their labia were not as small and/or symmetrical as they had expected. Most women reported significant improvements in their sexual well-being after surgery, however, some noted that their emotional discomfort around sexual intercourse had not improved. Conclusions: These new insights into why women seek labiaplasty, their experiences and outcomes may assist clinicians in enhancing their communication with prospective patients.